MALIGNANCY IN MULTINODULAR GOITER-POST THYROIDECTOMY: A PROSPECTIVE STUDY - Naeem, Fizza; Raza, Sayed Nusrat; Khan, Taimoor Ashraf (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the frequency and types of malignancy in patients treated surgically for nontoxicmultinodular goiter and its correlation in different age groups and gender.Study Design: Cross-sectional study.Place and Duration of Study: Department of ENT, Combined Military Hospital Rawalpindi, from Dec 2018 toDec 2019.Methodology: A total of 116 patients operated for nontoxic multinodular goiter were included in the study.Demographic details along with pre-op Ultrasonography findings, Fine Needle Aspiration Cytology, thyroidfunction test results and post-op histopathological reports of the thyroid specimen were entered on pre-designed proforma. Results were analyzed using the Statistical Package for Social Sciences (SPSS) Version 22.Results: Age ranges from 19 to 70 years (mean 43.51 years). Out of 116 cases operated for multinodular goiter,37 (31.8%) had malignant thyroid lesions (13 males, 24 females). Papillary carcinoma of the thyroid (45.9%) wasthe commonest malignancy followed by a follicular variant of papillary carcinoma (24.3%). The most common age group with malignancies was 49-58 years.Conclusion: Malignant Thyroid cancers showed a female preponderance and were most common in age group49-58 years. Papillary carcinoma of thyroid was the commonest tumor. Radical thyroid surgery is a recommended surgical management option for nontoxic Multinodular goiter.